Direct democracy and tax exporting: theory and an application to the first referendum ("consulta popular") in Argentina - Porto, Alberto (2002)
The assignment of the responsibility for different taxing powers is one of the most important problems in the theory and practice of fiscal federalism. The literature provides us with a set of general guidelines for the "tax assignment problem". One conclusion is that "tax exporting" could create perverse signals for fiscal choice. In this paper the tax exporting problem is analyzed with simple models. The case of a tax passed through a referendum (Consulta Popular) in an argentinean tourist Municipality is studied. In a numerical exercise, using the fiscal data of the Municipality, the size of the public expenditures is calculated under different rules of fiscal decision. Then, an empirical analysis of the results of the voting and its determinants is carried out. The paper concludes with some comments, in order to improve the mechanisms of referendum related to fiscal decisions at the municipal level.